Stepped care for depression at integrated chronic care centers (IC3) in Malawi: study protocol for a stepped-wedge cluster randomized controlled trial - Ryan K. McBain; Owen Mwale; Todd Ruderman; Waste Kayira; Emilia Connolly; Mark Chalamanda; Chiyembekezo Kachimanga; Brown David Khongo; Jesse Wilson; Emily Wroe; Giuseppe Raviola; Stephanie Smith; et al. (Trials, 2021)
Abstract Background Malawi is a low-income country in sub-Saharan Africa that has limited resources to address a significant burden of disease—including HIV/AIDS. Additionally, depression is a leading cause of disability in the country but largely remains undiagnosed and untreated. The lack of cost-effective, scalable solutions is a fundamental barrier to expanding depression treatment. Against this backdrop, one major success has been the scale-up of a network of more than 700 HIV clinics, with over half a million patients enrolled in antiretroviral therapy (ART). As a chronic care system with dedicated human resources and infrastructure, this presents a strategic platform for integrating depression care and responds to a robust evidence base outlining the bi-directionality of depression and HIV outcomes. Methods We will evaluate a stepped model of depression care that combines group-based Problem Management Plus (group PM+) with antidepressant therapy (ADT) for 420 adults with moderate/severe depression in Neno District, Malawi, as measured by the Patient Health Questionnaire-9 (PHQ-9) and Mini-International Neuropsychiatric Interview (MINI). Roll-out will follow a stepped-wedge cluster randomized design in which 14 health facilities are randomized to implement the model in five steps over a 15-month period. Primary outcomes (depression symptoms, functional impairment, and overall health) and secondary outcomes (e.g., HIV: viral load, ART adherence; diabetes: A1C levels, treatment adherence; hypertension: systolic blood pressure, treatment adherence) will be measured every 3 months through 12-month follow-up. We will also evaluate the model’s cost-effectiveness, quantified as an incremental cost-effectiveness ratio (ICER) compared to baseline chronic care services in the absence of the intervention model. Discussion This study will conduct a stepped-wedge cluster randomized trial to compare the effects of an evidence-based depression care model versus usual care on depression symptom remediation as well as physical health outcomes for chronic care conditions. If determined to be cost-effective, this study will provide a model for integrating depression care into HIV clinics in additional districts of Malawi and other low-resource settings with high HIV prevalence. Trial registration ClinicalTrials.gov NCT04777006 . Registered on 1 March, 2021